INSTITUSI QADA’ DALAM SEJARAH ISLAM - Mohamed Adil, Mohamed Azam (Jurnal Syariah, 2019)
Justice is an essence of Islamic teachings and no doubt a universal value. To uphold justice, Islam enjoins that those to be appointed as ~a.kim or qaq,l (judge) must meet certain criterias and certain characteristic. This article examines those criterias further.